Interlayer band alignment and electronic coupling effects at thiophene-based polymers/ReS2 van der Waals heterojunction - Garcia-Basabe, Yunier; Arce-Molina, Jorge; da Silva Lima, Bruno; Rodrigues, Daniel; Vicentin, Flavio C.; Steinberg, David; Thoroh de Souza, E. A.; Rocha, Alexandre R. [UNESP]; Larrude, Dunieskys G. (Elsevier, 2025)
In this study, we investigate two vdW heterojunctions, P3HT/ReS2 and PFO-DBT/ReS2, obtained by vertically stacking the thiophene-based semiconductor polymers poly(3-hexylthiophene-2,5-diyl) (P3HT) and Poly[2,7-(9,9-dioctylfluorene)- alt −4,7-bis(thiophen-2-yl) benzo-2,1,3-thiadiazole (PFO-DBT) with mechanically exfoliated ReS2. X-ray photoelectron spectroscopy (XPS) revealed that P3HT/ReS2 heterojunction, exhibits a type-I band alignment, with a valence band offset (VBO) of 0.32 eV and a conduction band offset (CBO) of 0.26 eV, positioning the conduction band minimum and valence band maximum within ReS2. In contrast, the PFO-DBT/ReS2 heterojunction exhibited a type-II band alignment, with the conduction band minimum in ReS2 and the valence band maximum in PFO-DBT, showing a VBO of −0.2 eV and a CBO of 0.59 eV. The distinct electronic coupling mechanisms in each heterojunction are attributed to the molecular-surface absorption geometry: a plane-on molecular orientation of P3HT polymer on the ReS2 surface induces interlayer electronic coupling through the electron rich π-system, whereas PFO-DBT exhibits lower molecular ordering on ReS2. The type-I and type-II band alignments observed in the P3HT/ReS2 and PFO-DBT/ReS2 heterojunctions, are consistent with the photoluminescence spectroscopy results. These findings suggest PFO-DBT/ReS2 is suitable for photovoltaic devices, while P3HT/ReS2 holds potential for LEDs.
Keywords: Band alignment; Electronic coupling; Organic/inorganic van der Waals heterojunction; ReS2; Thiophene-based polymers